New upper Homerian (uppermost Wenlock, Silurian) monograptids from Arctic Canada - Lenz, Alfred C. (Canadian Journal of Earth Sciences, 1994)
Five species of new or little-known upper Homerian (uppermost Wenlock) graptolites are described from the Arctic Islands. These are Lobograptus? sherrardae (Sherwin), Lobograptus? aff. sherrardae, Lobograptus? claudiae Koren, Lobograptus? cf. cornuatus Lenz, and "Pristiograptus" schedidoneus n.sp. The first- and last-named species range through the "Pristiograptus" praedeubeli and "Pristiograptus" ludensis biozones, that is, through the entire upper Homerian, whereas, the remaining three species appear to be confined to the (older) "P." praedeubeli Biozone. These species further document the rapid global evolution of the late Homerian graptolites, and this study records Lobograptus? claudiae Koren from outside central Asia for the first time.